PENERAPAN METODE MIND MAPPING DALAM MENINGKATKAN KEMAMPUAN MENULIS TEKS EKSPOSISI PADA SISWA KELAS X - Rivaldi Ramadhan; Wikanengsih Wikanengsih; Aditya Permana (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2020)
Researchers found problems in learning exposition text students still have difficulty in expressing ideas in the implementation of exposition text writing learning. Researchers use the mind mapping method as a way to provide stimulation to students in developing ideas or developing. The purpose of this research study is to study the differences and implementation of learning in students by using conventional methods and mind mapping methods in learning to write exposition text. The method used in this research is experimental type with the design used by One Group Pretest-Posttest Design. With the object of class X-MIA students who can be competed as many as 30 people. After spending is carried out using conventional methods and mind mapping methods in students in learning to write exposition text, then an assessment of the results obtained by the average score obtained. It can be seen from the results of the acquisition of pretest scores using the conventional method of 61.20 and an increase in the acquisition of posttest scores using the mind mapping method of 75.60 and an increase in the passing grade of students who exceeded the KKM which was originally only 7 people after being given treatment to 21 people.